METHANIZATION OF THE RESIDUAL BIOMASS OF TWO VARIETIES OF COCOA AND NUTRITIONAL CHARACTERIZATION OF THE BIODIGESTED SUBSTRATE - Zambrano-Gavilanes, Freddy (2021)
Anaerobic digestion enables the degradation of the biodegradable organic fraction present in solid waste, transforming it into biogas with high methane content and high energy use, and a fi nal residue with a high rate of destruction of pathogenic microorganisms which meets the conditions to be used as a soil improver and biofertilizer. In this context, the production of biogas and methane gas from the anaerobic digestion of two varieties of cocoa (CCN-51 and Nacional) was evaluated and the obtained substrate was nutritionally characterized. Th e following treatments were studied: T1 Shell CCN-51 (20% ST); T2 Shell CCN-51 (30% ST); T3 Slime CCN-51; T4 Shell CCN-51 + Slime CCN-51 (20% ST); T5 Shell CCN-51 + Slime CCN-51 (30% ST), T6 Shell Nacional (20% ST); T7 Shell de Nacional (30% ST); T8 Slime Nacional; T9 Shell de Nacional + Slime Nacional (20% ST); T10 Shell Nacional + Slime Nacional (30% ST); T11 Shell CCN-51 + Shell Nacional (20% ST); and T12 Shell CCN-51 + Shell from Nacional (30% ST). Biogas production was determined daily, and methane gas was also measured with the Orsat method. Physicochemical parameters of the biodigested substrates were analyzed. Th e T6 Shell Nacional (20% ST) was the most outstanding in the production of accumulated biogas (1297.66 mL) and in the percentage of methane gas (76%). Diff erent concentrations of macro and micronutrients were found in the biodigested biomass of the diff erent treatments, with potential for use as a biofertilizer in plants.